Heterogeneity in primary dystonia: Lessons from THAP1, GNAL, and TOR1A in Amish‐Mennonites. Issue 6 (5th February 2014) - Saunders‐Pullman, Rachel; Fuchs, Tania; San Luciano, Marta; Raymond, Deborah; Brashear, Alison; Ortega, Robert; Deik, Andres; Ozelius, Laurie J.; Bressman, Susan B.
ABSTRACT A founder mutation in the Thanatos‐associated (THAP) domain containing, apoptosis associated protein 1 (THAP1) gene causing primary dystonia was originally described in the Amish‐Mennonites. However, there may be both genotypic and phenotypic heterogeneity of dystonia in this population that may also inform studies in other ethnic groups. Genotyping for THAP1 and for guanine nucleotide binding protein (G protein), α‐activating activity polypeptide, olfactory type (GNAL) mutations and genotype‐phenotype comparisons were performed for 76 individuals of Amish‐Mennonites heritage with primary dystonia. Twenty‐seven individuals had mutations in THAP1—most with the founder indel mutation—but two had different THAP1 mutations, 8 had mutations in GNAL, and 1 had a de novo GAG deletion in torsin 1A (TOR1A) (dystonia 1 [DYT1]). In the primary analysis comparing THAP1 carriers versus all non‐THAP1, non‐GNAL, non‐TOR1A individuals, age at onset was lower in THAP1 carriers (mean age ± standard deviation, 15.5 ± 9.2 years [range, 5‐38 years] vs. 39.2 ± 17.7 years [range, 1‐70 years]; P < 0.001), and THAP1 carriers were more likely to have onset of dystonia in an arm (44.4% vs. 15.0%; P = 0.02) and to have arm involvement (88.9% vs. 22.5%; P < 0.01), leg involvement (51.9% vs. 10.0%; P = 0.01), and jaw/tongue involvement (33.3% vs. 7.5%; P = 0.02) involvement at their final examination. Carriers were less likely to have dystonia restricted to a single site (11.11% in carriers vs. 65.9% in noncarriers; P < 0.01) and were less likely to have dystonia onset in cervical regions (25.9% of THAP1 carriers vs. 52.5% of noncarriers; P = 0.04). Primary dystonia in the Amish‐Mennonites is genetically diverse and includes not only the THAP1 indel founder mutation but also different mutations in THAP1 and GNAL as well as the TOR1A GAG deletion. Phenotype, particularly age at onset combined with final distribution, may be highly specific for the genetic etiology. © 2014 International Parkinson and Movement Disorder Society